Viral and immune profiles during the first wave of SARS-CoV-2 infection in hospitalized patients in Sardinia, Italy - Giulietta Venturi; Alessandra Gallinaro; Claudia Fortuna; Maria Franca Pirillo; Arianna Scoglio; Beatrice Di Carlo; Giulia Marsili; Zuleika Michelini; Antonello Amendola; Alberto Carocci; Stefania Dispinseri; Martina Borghi; et al. (Scientific Reports)
Abstract We performed a retrospective immunological analysis of the antibody response in serum and in nasopharyngeal swabs (NPS) obtained from 46 individuals infected with ancestral SARS-CoV-2 Wuhan-Hu-1 strain during the first COVID-19 wave in Cagliari (Sardinia, Italy), with a 4-month follow-up after the hospital admission. We implemented a comprehensive antibody response in serum and in mucosal samples using assays established in our laboratories. In NPS we evaluated the viral load by real time PCR, presence and kinetics of anti-Spike IgG and IgA by ELISA as well as their anti-Wuhan neutralization activity, showing induction and persistence of anti-viral immunity at the mucosal level. Neutralizing antibodies were measured in serum and NPS using a safe pseudovirus-based assay validated after comparison with a standard neutralization test using live SARS-CoV-2. We evaluated cross-neutralizing antibodies against all the major early variants of concerns (VoC) in sera. Of note, we detected a remarkable reduction of neutralizing activity against BA.1 compared to BA.2 and BA.5 Omicron subvariants, which was confirmed in sera from an analogous cohort of patients at the San Raffaele hospital in Milan, a geographically distant region of Italy, infected with the ancestral virus during the same period of time.